PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE BAMBOO DANCING TERHADAP MINAT BELAJAR BAHASA INDONESIA SISWA KELAS V SD NEGERI 27 BULU DUA KABUPATEN SOPPENG - Nursamsilis Lutfin; Indria Purwati (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The influence of Cooperative Learning Model Bamboo Dancing Type on the interest in learning Indonesian language on folklore material in class V students of 27 Bulu Dua Elementary School Soppeng District. Whether there is any influence of Cooperative Learning Model Bamboo Dancing Type on the Interest of Learning Indonesian Language in Grade V Students of 27 Bulu Dua Elementary School in Soppeng District. The type of research used in this study was quantitative research with the research design is Pre-Experimental Design in the form of One-Group Pretest-Posttest Design. The research instruments used in this study were questionnaires and observation sheets. Data analysis techniques used were descriptive statistical analysis and inferential statistical analysis. The results of the study show that the cooperative dancing model bamboo dancing type, material in folktales has an influence on the interest in learning Indonesian in class V students of 27 Bulu Dua Elementary School in Soppeng District. This can be seen from the results of inferential analysis for interest in learning, from the results of the analysis of the hypothesis test data, namely 15.03 and t-table 1.72, then t-Calculate> t –table = 15.03> 1.72, the difference between the results of the pretest and posttest is significant, and it can be concluded that Ho is rejected and Hı is accepted means that the hypothesis in this study is accepted namely there is the influence of Cooperative Learning Model Bamboo Dancing Type on the interest in learning Indonesian language on folklore material in class V students of 27 Bulu Dua Elementary School Soppeng District